Why distributed leadership matters - Sesky, Jeanne. University of California, Los Angeles; Sesky, Jeanne (Center for Leadership Equity and Research)
This paper explores key findings from a study that examined how distributed leadership affected school turnaround at an underperforming urban high school. The study considers the presence of leadership as a distributive process, which is bound by action and not by role. How leadership was distributed across all tiers of the schools leadership structure was examined, ultimately resulting in dramatic turnaround. Additionally, the settings by which teachers, administrators, and support staff learned and thrived were examined; practices that these stakeholders believed made a difference for their students were also explored. Key to the sites shift was the collective foci on students. Each interviewee built to create a collective voice, celebrating their teamwork and their freedoms, from the district level down to the classroom level. No one setting or practice was touted as the fix for school change. Rather, study participants recognized the power of multiple settings and spoke of the necessity of each. They highlighted their personal connections, both at the site and within the community, stating its impact on school growth. Thus, this paper considers the impact of leadership when it is spread across many capable members of a school site.